Evidence for Resilient Agriculture (ERA): A launch event - Rosenstock, Todd S.; Lamanna, Christine; Namoi, Nictor; Kamau, Hannah N.; Steward, Peter R.; Nowak, Andreea C. (2019)
Presentation at the Global Science Conference for Climate-Smart Agriculture 8-11 October 2019. Bali, Indonesia.